Doğu Akdeniz’de Soğuk Savaş Dönemi Sovyet Faaliyetleri: Pyadyy Eskadra [Beşinci Filo] ve Türk Boğazları - İsmail KÖSE (Gazi Akademik Bakış)
Historical facts proved that it is impossible to be hegemon power without having domination on seas. Soviet rulers very-well aware of that fact, since the first years of the Cold War, tried to compete with Western Blok in the world seas especially on Mediterranean Sea where they recognized as their interest area. Due to problems occurred because of the shortages in the Soviet System, Soviets faced with grave challenges, tried to generate some ship building programs in order to lower that gap. The passage regime in the Turkish Straits which has been put into use by Montreux Convention, affected Soviet Mediterranean policy directly, Soviets struggled to solve that problem by establishing bases on coastline countries. Soviet Mediterranean Fleet Pyadyy Eskadra has been established under above conditions. The aim was to achieve Soviet hegemony in the Mediterranean. Soon after the deployment of Pyadyy Eskadra, Soviets struggled to transform emerging crisis in the south and southeastern Mediterranean coastline countries to empower their basis. Turkey’s policy to liberally comment and implement Montreux, contributed continuance of Soviet organic existence in the Mediterranean. The most challenging long lasting problem of Soviet Mediterranean Fleet Pyadyy Eskadra was absence of aircraft carrier. Despite aircraft carrier passage has been prohibited by Montreux, Turkey permitted Soviet aircraft carriers’ one way north-south passages which were built in the Black Sea shipyards and named with different classes. In this paper, considering Cold War rivalry conditions, Soviet Mediterranean Fleet Pyadyy Eskadra, Turkish Straits’ passage regime and US Mediterranean policies will be analyzed.